The optimisation of combustion systems for the burning of cereal straw as a fuel - Washbourne, John Fryer (1986)
International interest in fluidised bed combustion (F.B.C.) derives from the fact that it involves new technology and it is the only combustion system that can use low grade fuels (including those of high or variable ash content) efficiently. This thesis presents a study of the combustion of straw in a fully fluidised and systematically interrupted flow test rig. In the interrupted flow mode, it was found that during the period in the cycle when the bed was slumped, due to the reduction in primary air, a gasification process took place. This resulted in a higher percentage of volatiles being burned in the bed and preliminary results indicated that interruption gave an increase in overall efficiency of approximately 4%. It also led to lower losses being incurred in the flue gases and, to a lesser extent, to a reduction in the losses expected due to incomplete combustion of the fuel. Elutriation and carbon losses were also reduced to 88% and 86% respectively of those recorded during uninterrupted fluidisation. By increasing the area of the zone directly above the fluidised bed, the products of combustion were decelerated sufficiently to ensure that ash was not found on the walls or roof to the same extent as that previously noticed on commercial straight-sided combustion chambers. Small quantities of ash were found in the ducting leading to the cyclone but they were approximately the same for operation in both the uninterrupted and interrupted fluidisation mode.